The radical anion, dianion and electron transport properties of tetraiodotetraazapentacene - Wiesner, Thomas; Wu, Zhu; Han, Jie; Ji, Lei; Friedrich, Alexandra; Krummenacher, Ivo; Moos, Michael; Lambert, Christoph; Braunschweig, Holger; Rudin, Benjamin; Reiß, Hilmar; Tverskoy, Olena; et al. (Chemistry - a European journal, 2022)
Tetraiodotetraazapentacene I4TAP, the last missing derivative in the series of halogenated silylated tetraazapentacenes, was synthesized via condensation chemistry from a TIPS-ethynylated diaminobenzothiadiazol in three steps. Single and double reduction furnished its air-stable monoanion and relatively air-stable dianion, both of which were characterized by crystallography. All three species are structurally and spectroscopically compared to non-halogenated TAP and Br4TAP. I4TAP is an n-channel material in thin-film transistors with average electron mobilities exceeding 1 cm2 (Vs)−1.